Formal Finance and Trade Credit During China's Transition - Cull, Robert; Xu, Lixin Colin; Zhu, Tian (World Bank, Washington, DC, 2012)
Using a large panel dataset of Chinese industrial firms, the authors examine the determinants of access to loans from formal financial intermediaries and extension of trade credit. Poorly performing state-owned enterprises were more likely to redistribute credit to firms with less privileged access to loans through trade credit, a pattern consistent with some of the extension of trade credit being involuntary. By contrast, profitable private domestic firms were more likely to extend trade credit than unprofitable ones. Trade credit likely provided a substitute for loans for these private firms' customers that were shut out of formal credit markets. As biases in lending became less severe, the amount of trade credit extended by private firms declined.